Rage at dawn - Whelan, Tim, 1893-1957; Scott, Randolph, 1898-1987; RKO Radio Pictures; Cinetel Films ([Los Angeles, CA] : RKO Radio Pictures, Inc., 1955)
Terrorizing 1866 Indiana, the Reno brothers gang uses the town of Seymour as a safe haven, paying off three crooked town officials. Sent in to clean up the gang is Peterson Detective Agency operative James Barlow, who poses as an outlaw to gain the confidence of the officials and the thick-headed brothers. Complicating matters are Barlow's feelings for the Reno sister, Laura, who reluctantly keeps house for the boys out of family loyalty. Events heat up and rage surfaces as Barlow sets up the gang in a dawn train robbery. --
Randolph Scott, Forrest Turker, Mala Powers, J. Carrol Naish
Cinematographer, Ray Rennahan; editor, Harry Marker; music, Paul Sawtell.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Reno Brothers -- Drama; Outlaws -- Indiana -- Drama; Lynching -- Indiana -- Drama; Western films; Feature films; Internet videos; Streaming video